Plan of Action of the Fourth Summit of the Americas: Creating Jobs to Fight Poverty and Strengthen Democratic Governance - (:unkn) unknown (My University, 2016)
The region´s Heads of State and Government concluded the Fourth Summit of the Americas Saturday evening, after adopting a political declaration and an ambitious plan of action designed to create jobs, combat poverty and strengthen democratic governance.